2003
DOI: 10.1063/1.1593801
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of photoluminescent defect clusters in proton- and copper-implanted silicon crystals during annealing

Abstract: Evolution of intrinsic defects (interstitials or vacancies) formed by implanting with protons and copper ions in silicon crystals and then annealing the crystals at temperatures from 100 to 800 °C was investigated by photoluminescence (PL) measurements. For samples annealed below 400 °C, only the well known W and I3 center peaks were observed for both proton and copper implantations. Several no-phonon PL peaks (at least six), that were inferred to be due to interstitial clusters, were newly evolved between 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…26,27 The earlier inverse model studies suggested that there would be a structural transition from compact to elongated forms when the cluster size ͑n͒ is around 10 atoms, and also the differential formation energies of small clusters ͑n Ͻ 10͒ exhibit two strong minima at n = 4 and n = 8. The predictions were also advocated by recent low temperature photoluminescence studies [22][23][24] which demonstrated possible existence of small and compact interstitial clusters of various sizes. The minimum-energy configurations of a few small clusters ͑n =1-5͒ have recently been determined using extensive firstprinciples-based atomistic simulations.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…26,27 The earlier inverse model studies suggested that there would be a structural transition from compact to elongated forms when the cluster size ͑n͒ is around 10 atoms, and also the differential formation energies of small clusters ͑n Ͻ 10͒ exhibit two strong minima at n = 4 and n = 8. The predictions were also advocated by recent low temperature photoluminescence studies [22][23][24] which demonstrated possible existence of small and compact interstitial clusters of various sizes. The minimum-energy configurations of a few small clusters ͑n =1-5͒ have recently been determined using extensive firstprinciples-based atomistic simulations.…”
Section: Introductionmentioning
confidence: 67%
“…20 Hence, most interstitials are likely to remain in the form of clusters in bulk Si. 3,4 While extended ͕311͖ defects have been well characterized by transmission electron microscopy, earlier spectroscopy measurements based on deep level transition, 21,22 photoluminescence, [22][23][24] and electron spin resonance 25 have also evidenced the formation of small interstitial clusters ͑Ͻ50 Å in equivalent diameter͒ at low doses ͑10 12 -10 14 Si/ cm 2 ͒ and moderate annealing temperatures ͑ഛ600°C͒ before they evolve into larger extended defects with increased ion fluence ͑ജ5 ϫ 10 13 Si/ cm 2 ͒ and elevated annealing temperatures ͑ജ700°C͒. In fact, in ultrashallow junction formation with low-energy implanted dopants, small self-interstitial clusters are thought to be a main source for free interstitials responsible for dopant TED and clustering during postimplantation annealing.…”
Section: Introductionmentioning
confidence: 99%
“…This prediction has been supported by a series of low-temperature photoluminescence ͑PL͒ studies 7,9,10 which show the signatures of small compact clusters of various sizes in ion-implanted Si upon short annealing. In addition, the PL measurements demonstrate changes in the spectra from multiple sharp peaks to broad but distinct signatures during prolonged annealing, ascribed to the shape evolution of self-interstitial clusters from compact to extended forms.…”
Section: Introductionmentioning
confidence: 78%
“…The formation and structure of rodlike ͕311͖ defects have been well characterized by high-resolution transmission electron microscopy ͑HRTEM͒. [3][4][5] In addition, a series of recent spectroscopy measurements [6][7][8][9][10][11] have evidenced existence of small compact self-interstitial clusters before they evolve into larger extended defects. In ultrashallow junction formation with low-energy implanted dopants, such small interstitial clusters are thought to be a main source for free interstitials responsible for dopant transient enhanced diffusion and agglomeration during postimplantation thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 We report here on the interstitial/vacancy nature of luminescence centers created when silicon is implanted at room temperature with MeV Si + ions and subsequently annealed. 2 Some PL centers have recently been associated with interstitial clusters, 3 on the basis of their stability at 600°C, well above the annealing temperature of vacancy defects measured by deep level transient spectroscopy ͑DLTS͒ on lowdose implanted samples. 1͒, PL can unambiguously monitor each specific defect.…”
Section: Identification By Photoluminescence and Positron Annihilatiomentioning
confidence: 99%